Factors affecting the surgical outcome of patients with cerebral contusions - Akyam, Lakshman Rao; Gudla, Venugopal; Jyothi, Sangam M. (International Surgery Journal, 2016)
Background:Study of factors influencing mortality after cerebral contusion is useful for clinicians to predict outcome of such patients. Hence present study was undertaken with the objective to analyse the factors affecting the surgical outcome of patients with cerebral contusions. Methods: This is a prospective study consisting of 187 cases of cerebral contusions operated in a period from August 2005 to Feb 2008, in the Department of Neurosurgery, Osmania General Hospital, Hyderabad. During the period of study total numbers of head injury admissions were 8163, out of which 964 cases were of cerebral contusions. Among them 187 cases underwent operation. All the patients underwent all necessary investigations. The data was analysed using proportions and appropriate statistical test wherever applicable. Results:Males were more than females but mortality rate was comparable. Most of the contusions were in 20 -40 years of age. Road traffic accidents were the commonest mode of injury. Most of the cases were moderate of server type of head injuries. The mortality rate in the severe head injury was 33%. Frontal and Temporal locations were the commonest site of contusion and the surgical outcome was better in frontal and temporal than parietal and cerebellar contusions. The overall mortality was 21%. It is seen that age more than 30 years, severe GCS and midline shift of more than 5 mm were the important predictors of mortality after surgery for cerebral contusions. Conclusions:Age more than 30 years; severe GCS and midline shift of more than 5 mm were the important predictors of mortality after surgery for cerebral contusions.